Радiацiйно-стимульоване формування “важких кластерiв” в бiнарних кристалах - Mykytenko, N. (Publishing house "Academperiodika", 2019)
Radiation-induced formation of defects in binary crystals with significantly different atomic masses has been studied. The classical molecular dynamics method is used for a modified model that is an alternative for that with pair collisions. A computer program realizing the Verlet algorithm in the framework of the molecular dynamics approach is developed. The results obtained testify to the existence of a certain interval of incident particle energies, at which the so-called “heavy” clusters, i.e. clusters composed of heavier atoms, can be formed.